Cooking by color for health, fitness and energy : 50 recipes shown step by step in over 300 photographs - Davies, Trish (Lorenz Books, 2010)
This essential book provides fun and interesting ways to help make eating by color for health not only possible but easy for everyone. 50 tempting recipes make the rainbow diet easy and fun, proving that healthy food can be enjoyable